Congruity Theory Dan Komentar Netizen Terkait Taman Mini Indonesia Indah (TMII) - Rachmaniar, Rachmaniar; Anisa, Renata (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
Taman Mini Indonesia Indah (TMII) is a cultural tourism complex in Jakarta, which in 2023 will undergo a revitalization process aimed at improving the quality and experience of visiting tourists. TMII has attracted the attention of tourists to visit it. It is not surprising that if you open the YouTube social media platform and look for information about TMII, netizens will find many videos covering TMII. One of the videos that provides information about TMII is a video from the CNBC Indonesia YouTube channel. This six-minute video has been watched more than 95 thousand times, and invited many comments. Based on these facts, the author is interested in analyzing netizen comments regarding this tourism video. To answer this question, the author uses the virtual ethnographic research tradition, with data analysis based on congruity theory. The research results show that 1) netizens' appreciation regarding TMII and the existence of CNBC Indonesia journalist Shania Alatas are the things that netizens say most often in the comments column on the video This is the New Face of Taman Mini Indonesia Indah on the CNBC Indonesia YouTube channel; 2) comments regarding netizens' appreciation of TMII and the existence of CNBC Indonesia journalist Shania Alatas in line with Osgood and Tannebaum's congruity theory; 3) Shania Alatas conveyed a message about TMII that could be positive (associative) to netizens.